HUKUM KELUARGA DI AFGHANISTAN - Hasbollah Toisuta (TAHKIM, 2017)
The family law on its development gets government and scholar attention in the Islamic world, included in Afghanistan. It is interesting to investigate given has been enacted the marriage law, Qanun-i Izdiwaj in 1971 in Afghanistan based on the Egyptian Family Law in 1929 and fully enforce the Maliki’s law on the women rights to file divorce in the court. In addition, the provisions of this law amended the practices prevailing locally related to marriage and divorce. Although in some cases are still bound to the Hanafi school fiqh, the family law in Afghanistan has undergone reformation in line with the modern world development. The reformation system of its family law leads to extra doctrinal reform, by way of giving new interpretation, which sometimes differ from the provisions of Hanafi’s school followed by majority of its population. The reformation material of family law undertaken in Afghanistan, is the dowry, child marriage, polygamy and divorce. Keywords: reformation, family law, Afghanistan